Expression of CXCR4 and CXCL12 and their correlations to the cell proliferation and angiogenesis in mycosis fungoides - Maj, Joanna; Jankowska-Konsur, Alina M.; Hałoń, Agnieszka; Woźniak, Zdzisław; Plomer-Niezgoda, Ewa; Reich, Adam (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Chemokines play an important role in tumor growth, invasion and metastasis. The CXCR4/CXCL12 axis has been implicated in development of both solid tumors and hematological malignancies and is also relevant in the pathogenesis of the most common primary cutaneous T-cell lymphoma, mycosis fungoides (MF). Aim: To evaluate the expression of CXCR4 and CXCL12 in MF and to examine their associations with cell proliferation and angiogenesis. Material and methods : The material for the study consisted of skin samples obtained from 56 patients with MF and 20 healthy volunteers. The expression of CXCR4 and CXCL12 was assessed by immunohistochemistry on the paraffin blocks and compared to the expression of angiogenesis marker (CD34) and proliferation indicators (Ki-67, AgNORs). Results : The expression of chemokine CXCL12 and its receptor CXCR4 was significantly higher in MF than in the healthy skin (p < 0.001). There was no significant difference between early and advanced stages of MF. Similarly, there was no statistically important correlation between the expression of CXCR4/CXCL12 and angiogenesis and proliferation markers, however a significant correlation between CD34 and AgNORs expression was found (p < 0.001). Conclusions : The CXCR4/CXCL12 axis seems to play an important role in MF development in the early as well as in the advanced stages of the disease. Therefore, the CXCR4/CXCL12 axis seems to be an interesting potential target for the future strategies of new drug development, giving hope for more efficacious therapies for mycosis fungoides.